(untitled) (Research, Society and Development, 2021)
The national system for the exploitation of industrial property, whose protection works through the granting of patents and registrations, is relevant to the country’s technological development. In the case of patents, the large increase in requests generates what has been called a backlog, requests pending for longer than the intended duration. As a way to fight backlog, the INPI has been improving the priority process of processes. The objective of this work is to discuss the relevance of the priority patent procedures related to ICTs. The methodology adopted in this research is based on the assumptions of a quali-quantitative approach, setting up a research of a basic nature, with an exploratory objective, with data collection procedures carried out through bibliographical and documentary research. We found that the patent backlog is still a serious problem that Brazil is facing, with an increasing demand for new analysis of these assets. The initiative to promote a priority procedure for ICTs configures a national strategic process within the scope of the Brazilian innovation system that tends to promote benefits, not only for these institutions, but also the generation, at some point, of social well-being.